Testosterone replacement therapy and the risk of venous thromboembolism: A systematic review and meta-analysis of randomized controlled trials. Issue 199 (March 2021) - Ayele, Henok Tadesse; Brunetti, Vanessa C.; Renoux, Christel; Tagalakis, Vicky; Filion, Kristian B.
Abstract: Introduction: The cardiovascular safety of testosterone replacement therapy (TRT) is controversial. While several studies have investigated the association between TRT and the risk of arterial thrombosis, limited information is available regarding its risk of venous thromboembolism (VTE). We aimed to compare the risk of VTE in men randomized to TRT versus placebo or active-comparator in a systematic review. Methods: We searched Medline, EMBASE, CINAHL, CENTRAL, and clinical trial registries to identify randomized controlled trials (RCTs) comparing TRT to placebo in men aged ≥18 years. We assessed study quality using the Cochrane Risk of Bias assessment tool and the overall quality of evidence using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria. Data were pooled across RCTs using random-effects models. Results: A total of 13 RCTs ( n  = 5050) were included in our meta-analysis. In all, 2636 men were randomized to testosterone, and 2414 men to placebo. Sample sizes ranged from 101 to 790 men, and TRT duration from 3 to 36 months. Five studies had a high risk of bias, largely driven by unclear randomization and outcome assessment. When data were pooled across RCTs, testosterone therapy was not associated with VTE compared with placebo (RR: 1.03, 95% CI: 0.49–2.14; I 2 : 0%; low-quality evidence). Similar estimates were obtained for deep vein thrombosis and pulmonary embolism outcomes. Conclusions: Our systematic review suggests that TRT is not associated with an increased risk of VTE. However, estimates were accompanied by a wide 95% CIs, and a clinically important increased risk cannot be ruled out. Highlights: In the last 3 decades, testosterone use has increased 10-fold in North America. However, the cardiovascular safety of testosterone use has remained controversial. Our meta-analysis of randomized trials examined the VTE risk of testosterone use. We found no evidence of an increased risk of VTE with testosterone use. Given the low quality of evidence, there is a need for further studies in this area.